2020
DOI: 10.1097/ta.0000000000002818
|View full text |Cite
|
Sign up to set email alerts
|

The use of warm fresh whole blood transfusion in the austere setting: A civilian trauma experience

Abstract: BACKGROUND Hemostatic resuscitation strategy using blood components with a balanced ratio is adopted in the civilian trauma setting. However, there is usually limited availability of blood components in the austere setting. Warm fresh whole blood (WFWB) has been used for trauma patients with life-threatening hemorrhage necessitating massive transfusions in the Okinawa Islands, Japan. The purpose of this study was to evaluate the safety and feasibility of WFWB use in the austere civilian trauma sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We identified 17 studies reporting about patients with traumatic hemorrhage treated with at least 1 unit WB (without BCT comparison) including 10 retrospective cohort studies, 4 case series, and 3 prospective observational studies 12,14,58–72 . All studies are summarized in Supplementary Digital Content 13, http://links.lww.com/TA/D6.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 17 studies reporting about patients with traumatic hemorrhage treated with at least 1 unit WB (without BCT comparison) including 10 retrospective cohort studies, 4 case series, and 3 prospective observational studies 12,14,58–72 . All studies are summarized in Supplementary Digital Content 13, http://links.lww.com/TA/D6.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 17 studies reporting about patients with traumatic hemorrhage treated with at least 1 unit WB (without BCT comparison) including 10 retrospective cohort studies, 4 case series, and 3 prospective observational studies. 12,14,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] All studies are summarized in Supplementary Digital Content 13, http://links.lww.com/TA/D6. In brief, included studies reported that WB transfusion is feasible in both military medicine, 62,68 and civilian medicine, 12,70,71 including in the prehospital setting.…”
Section: Wb Transfusion Without Bct Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemorrhagic shock after trauma is a much more common cause of death in military personnel and civilians than trauma alone. Particularly in the civilian population, there is higher mortality due to extremity/penetrating injuries (19)(20)(21)(22). Volume expansion for traumatic HS can be achieved via crystalloid resuscitation to restore tissue perfusion and plasma resuscitation to replace the crystalloid (23).…”
Section: Discussionmentioning
confidence: 99%